Population fluctuation of Rotylenchulus reniformis in soil cultivated with cotton - Asmus, Guilherme Lafourcade; Ishimi, Cassiana Miki (Pesquisa Agropecuaria Brasileira, 2009)
The objective of this work was to determine the population fluctuation of reniform nematodes (Rotylenchulus reniformis) in a cotton production area as affected by soil and climate conditions. A grid of 30 sampling sites, equidistant in 50 m from each other, was established in a field naturally infested – with an average of 680 reniform nematodes per 200 cm3 soil, in Aral Moreira county, Mato Grosso do Sul, Brazil. Soil samples at 0.0–0.2 and 0.2–0.4 m depths were collected monthly on each sampling site, between October 2004 and June 2006, for the evaluation of nematode abundance and population composition. Measurements of soil temperature and moisture at 0.15 and 0.30 m depth and rainfall were made in each sampling site. It was observed that cotton plants play important roles in the abundance and composition of reniform nematode populations. The abundance of R. reniformis was higher at 0.2–0.4 m depth. Rainfall and soil moisture contents had little influence on reniform nematode population. Soil temperatures at both 0.15 and 0.30 m were correlated to R. reniformis population density at 0.2–0.4 m depth.